2006
DOI: 10.1002/cne.21005
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical connections of anterior and posterior parietal cortical areas in New World titi monkeys

Abstract: We examined the thalamocortical connections of electrophysiologically identified locations in the hand and forelimb representations in areas 3b, 1, and 5 in the New World titi monkeys (Callicebus moloch), and of area 7b/AIP. Labeled cells and terminals in the thalamus resulting from the injections were related to architectonic boundaries. As in previous studies in primates, the hand representation of area 3b has dense, restricted projections predominantly from the lateral division of the ventral posterior nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 77 publications
5
13
0
Order By: Relevance
“…Previous studies have not revealed notable differences in the somatotopic organization in the thalamus and area 3b in these two species (Nelson and Kaas 1981; Nelson et al 1980; Padberg and Krubitzer 2006; Jones and Friedman 1982). MM-D was born with a deformed left foot (Fig.…”
Section: Methodsmentioning
confidence: 59%
“…Previous studies have not revealed notable differences in the somatotopic organization in the thalamus and area 3b in these two species (Nelson and Kaas 1981; Nelson et al 1980; Padberg and Krubitzer 2006; Jones and Friedman 1982). MM-D was born with a deformed left foot (Fig.…”
Section: Methodsmentioning
confidence: 59%
“…In macaque monkeys (Nelson and Kaas 1981; Darian-Smith et al 1990), squirrel monkeys (Jones 1975; Cusick et al 1986), owl monkeys (Lin et al 1979), titi monkeys (Coq et al 2004; Padberg and Krubitzer 2006), cebus monkeys (Mayner and Kaas 1986), and marmosets (Krubitzer and Kaas 1992) the ventral posterior nucleus has dense projections to area 1. We also observed moderate projections from VPs, Pla and VPi (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, invasive studies in non-human primates [48][50] and in vivo studies in humans [51], [52] showed that some of the cortical structures lesioned in pusher syndrome, namely the insular cortex and the postcentral gyrus [16], have direct connections with the ventroposterior and the lateral posterior nuclei of the posterior thalamus, i.e. with those thalamic strucutres typically found affected when patients exhibit pushing behaviour [13], [15].…”
Section: Discussionmentioning
confidence: 99%